Differential impacts of wildfire on the population dynamics of an old‐forest species. Issue 6 (2nd May 2017) - Rockweit, Jeremy T.; Franklin, Alan B.; Carlson, Peter C.
Abstract: Ecological disturbances shape and maintain natural communities, but climate change and human land use can alter disturbance regimes and affect population persistence and vital rates in unpredictable ways. Species inhabiting landscapes shaped by wildfire have evolved mechanisms allowing them to persist under this dynamic disturbance type, which creates habitats of varying quality for these species. We utilized data from a 26‐yr demographic study of northern spotted owls to analyze the influence of wildfire on apparent survival and recruitment rates. Wildfires occurred across different years and affected different spotted owl territories, which allowed us to implement a retrospective Before‐After‐Control‐Impact (BACI) analysis and model the potential effect of wildfire extent and severity. Our results indicated that mixed‐severity fires that burned at predominantly low‐severity had little effect on survival and recruitment while fires characterized by more medium to high burn severities negatively affected spotted owl survival, with varying effects on recruitment. Reduced survival and increased recruitment rates on some territories affected by medium to high severity fires suggested that post‐fire habitat quality was reduced resulting in territories that were marginally capable of supporting owls. We hypothesize these territories may have represented "sinks" that were supported by nearby "source" territories in a spatially heterogeneous landscape created by the mixed‐severity fire regime of the region.